EXTENSION PROGRAM IN CEFD/UFES AQUATIC ACTIVITIES: SERVICE PROPOSAL TO THE COMMUNITY (Fiep Bulletin - online, 2015)
The Physical Education and Sports Center of Universidade Federal do Espírito Santo began the Extension and Social Development Program, in April of 2005, this program counts on several corporal practices that seek to assist the community in general, hydrogymnatics being among them. The search for hydrogymnatics classes was exclusively by feminine public, with differentiated purposes, as medical recommendation, for presenting anomalies or osteoarticular pathology, as  osteoporosis and arthrosis. The article aimed at introducing a methodological proposal of hydrogymnatics activities that seeks to minimize the damages caused by arthrosis and osteoporosis, providing improvements in several functions of the individuals who have those pathologies. In order to do it, a survey of the theoretical references that debate the hydrogymnatics, osteoporosis and arthrosis theme was accomplished .It is evident in the literature that, after initiated the pathological process of articular wearing out and bone loss, the most that can be done is to minimize these disorders. Healthy life habits and the practice of physical activities are fundamental during a lifetime. Then It is concluded that hydrogymnatics has positive effects in those individuals' treatment, mainly concerning secondary factors, but it cannot be used as the unique treatment.
Keywords: Hydrogymnatics. Osteoporosis. Arthrosis.